ANALISIS MARSHALL CAMPURAN AC-WC DENGAN BUTON GRANULAR ASPHALT DAN ABU CANGKANG KELAPA SAWIT SEBAGAI BAHAN SUBSTITUSI - Rahmadi Rahmadi; Sofyan M. Saleh; Renni Anggraini (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Flexible Pavement often experience an early collapse resulting from high temperatures and heavy loads in the field. One way to overcome the damage, by using added materials to modify the asphalt. In this study the added ingredients used were Buton Granular Asphalt (BGA) as an asphalt and aggregate substitution on AC-WC mixture and utilization of ash waste of palm kernel shell (APKS) as filler substitution material. The purpose of this research is to know the comparison of AC-WC mixture’s characteristics with and without BGA and APKS as substitution materials. The first step of this research was to examine the physical properties of bitumen and aggregate, then made the specimens for determination of Optimum Asphalt Content (OAC) either without or with variations of BGA percentage of 4%, 6% and 8%. After OAC using the BGA acquired then OAC were varied to OAC-0,5; OAC and OAC+0,5 for subsequent test specimens with APKS filler and portland cement respectively 50% of total filler’s weight by Marshall method. Based on the result of this research, OAC value obtained in the mixture without BGA and APKS was 5,31%, whileeffective asphalt content value with BGA and APKS substitution obtained at 6,54% atlevel of 8% BGA. The Marshall’scharacteristic values using APKS and BGA tended to be better than those without BGA and APKS. Stability value of asphalt mixture without substitution was 1,602.84 kg while using BGA and APKS was 2,223.93 kg. Value of density, flow and VFA increased with increasing asphalt content in the mixture, while VIM, VMA and MQ value decreased. The durability value of AC-WC mixture with effective BGA was 95.90%, while the durability value without BGA and APKS was 92.76%. Durability value without and with substitution of BGA and APKS hadfulfilled requirement that was greater than 90%.